Anterior Cruciate Ligament Reconstruction in Patients with Open Physes: Early Outcomes - Csintalan, Rick P.; Inacio, Maria C.S.; Desmond, Jamie L.; Funahashi, Tadashi T. (The Journal of Knee Surgery, 2013)
Both nonoperative and operative treatments for anterior cruciate ligament (ACL) deficient knees in skeletally immature patients have reported potentially negative outcomes. This study describes primary ACL reconstruction patients with open physes and their concurrent injuries and evaluates whether these patients are at a higher early risk of revision and reoperation than closed physes patients. A retrospective analysis of prospectively collected data was performed. Patients were identified using an ACL Reconstruction Registry. Summary statistics comparing open and closed physes patients of similar ages in regard to patient characteristics and incidence of early revision and reoperation are provided. Adjusted Cox regression models assessed risk of early revision and reoperation for open physes patients. Of 1,867 patients identified, 232 (12.4%) patients had open physes and 1,635 (87.6%) patients had closed physes. Patients with open physes were younger, less likely to be women, and had less medial meniscal injuries than closed physes patients. No significant differences were observed in cartilage injury, overall menisci injury and repair, and early revision and reoperation rate. According to the our results, no significant differences in risk of early revision or early reoperation in open physes compared with closed physes patients when adjusting for age were observed, nor were there any reoperations for physeal closure.
Keywords: anterior cruciate ligament reconstruction; open physis; skeletally immature patients; risk of revision; reoperation